High-Efficiency and High-Performance Power Electronics for Power Grids and Electrical Drives - Luna, Massimiliano (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint collects papers addressing valuable techniques to improve the efficiency and performance of power electronics when applied to power grids and electrical drives. The proposed techniques leverage several approaches, e.g., advanced converter topologies, innovative control algorithms, and wide bandgap power devices. Diverse application domains were covered: interfacing Renewable Energy Sources (RESs) and Energy Storage Systems (ESSs) with AC or DC microgrids; recharging ESSs in electric vehicles; increasing performance in variable speed electrical drives and direct online induction motors; applying electrical loss minimization techniques to microgrids based on RESs. After a short description of each contribution, some perspectives for future developments are also briefly given.